The effect of investment, education level, and government spending on economic growth and labor absorption in East Kalimantan Province, Indonesia - Listiyono, Nidya; Wijaya, Adi; Tricahyadinata, Irsan (Technium Social Sciences Journal, 2021)
To spur the rate of economic growth and labor absorption, a special scheme is needed that is linked with the role of the private sector (investment) and government policy intervention through the allocation of expenditure, so as to create sustainable human resources interpreted by the intensity of education. The objectivity of the study focuses on the identification of investment, level of education, and government spending so that is known the extent of their role in economic growth and labor absorption in East Kalimantan Province. Time-series data processing during the period 2009-2019 is supported by quantitative techniques, making it easier for researchers to measure the accuracy of the unit in each variable. The study coverage only covers the province of East Kalimantan. Then, the data are interpreted through path analysis, where the output is aimed at three steps (direct effect, indirect effect, and total effect). Several things can be concluded to answer the objectives of the study, namely that investment and government spending directly have a positive-significant effect on economic growth. On the one hand, only the level of education has a significant positive effect on labor absorption. For the indirect effect, where economic growth is an intervening variable, the result is that investment and government spending both have a positive effect, but have no significant effect on labor absorption through economic growth.